Experimental Investigation on the Material Removal of the Ultrasonic Vibration Assisted Abrasive Water Jet Machining Ceramics - Tao Wang; Rongguo Hou; Zhe Lv (Advances in Materials Science and Engineering)
The ultrasonic vibration activated in the abrasive water jet nozzle is used to enhance the capability of the abrasive water jet machinery. The experiment devices of the ultrasonic vibration assisted abrasive water jet are established; they are composed of the ultrasonic vibration producing device, the abrasive supplying device, the abrasive water jet nozzle, the water jet intensifier pump, and so on. And the effect of process parameters such as the vibration amplitude, the system working pressure, the stand-off, and the abrasive diameter on the ceramics material removal is studied. The experimental result indicates that the depth and the volume removal are increased when the ultrasonic vibration is added on abrasive water jet. With the increase of vibration amplitude, the depth and the volume of material removal are also increased. The other parameters of the ultrasonic vibration assisted abrasive water jet also have an important role in the improvement of ceramic material erosion efficiency.